Microbiota Detection Patterns Correlate With Presence and Severity of Barrett’s Esophagus - Okereke, Ikenna C.; Miller, Aaron L.; Jupiter, Daniel C.; Hamilton, Catherine F.; Reep, Gabriel L.; Krill, Timothy; Andersen, Clark R.; Pyles, Richard B. (Frontiers in Cellular and Infection Microbiology, 2021)
Background The microbiome has been increasingly associated with different disease processes, but its role in esophagus is largely unknown. Our goal was to determine the associations of the esophageal microbiota with Barrett’s esophagus. Methods A total of 74 patients were included in this prospective study, including 34 patients with Barrett’s esophagus and 40 patients without Barrett’s esophagus. Esophageal swabs were obtained from the uvula, and mucosal biopsies were obtained from the proximal esophagus and distal esophagus in each patient. The microbiome of each sample was assessed using a customized Esophageal Microbiome qPCR array (EMB). For each clinical sample, we completed a detection/non-detection analysis for each organism in the EMB. The limit of detection (LOD) for each target was established by analysis of plasmid dilutions. Results Average age was 60.2 years. There were significantly different microbial detection patterns in patients with Barrett’s esophagus compared to the control population. There were a greater number of organisms which had different likelihoods of detection in the distal esophagus, compared to the proximal esophagus or uvula. In addition, as the length of the Barrett’s column increased, multiple organisms were less likely to be detected. This decreased likelihood occurred only in the distal esophagus. Beside Barrett’s esophagus, no other demographic factors were associated with differences in detection patterns. Conclusions Microbial community structures differ between patients with and without Barrett’s esophagus. Certain organisms are less likely to be detected as the severity of Barrett’s esophagus worsens. These results suggest that particular organisms may have a protective effect against the development of Barrett’s esophagus.